THE EFFECT OF E-FILLING, TAX AWARENESS AND KNOWLEDGE ON SOUTH BATAM TAXPAYER COMPLIANCE - Mika Maranata Sitompul; Poniman Poniman (Jurnal Ekonomi, 2023)
The level of taxpayer compliance at KPP Pratama Batam Selatan has experienced ups and downs but the level is still said to be quite far from the worst in 2018 to 2021. There are various factors that can affect taxpayer compliance including e-filling, awareness and tax knowledge. The purpose of this study is to test and evaluate partially and simultaneously whether e-filling, awareness and knowledge affect individual taxpayer compliance at KPP Pratama Batam Selatan. This type of research is quantitative with primary data sources obtained through questionnaires. The population in this study is all individual taxpayers (WPOP) in KPP South Batam which amounts to 353,613 taxpayers. The samples in this study used random sampling techniques and sample determination using slovin which amounted to 100 respondents. The results of the study partially showed that E-Filing has a significant effect on individual taxpayer compliance in KPP Pratama Batam Selatan, tax awareness has a significant effect on individual taxpayer compliance at KPP Pratama Batam Selatan, tax knowledge has a significant effect on individual taxpayer compliance at KPP Pratama Batam Selatan. Simultaneously, E-Filing, Tax Awareness and Taxation Knowledge simultaneously have a significant effect on individual taxpayer compliance at KPP Pratama Batam Selatan. The conclusion of the study is that H1 is accepted, H2 is accepted, H3 is accepted and H4 is accepted.